Building Statewide Infrastructure for the Academic Support of Students With Mild Traumatic Brain Injury. Issue 6 (November 2016) - Gioia, Gerard A.; Glang, Ann E.; Hooper, Stephen R.; Brown, Brenda Eagan
Abstract : Objectives: To focus attention on building statewide capacity to support students with mild traumatic brain injury (mTBI)/concussion. Method: Consensus-building process with a multidisciplinary group of clinicians, researchers, policy makers, and state Department of Education personnel. Results: The white paper presents the group's consensus on the essential components of a statewide educational infrastructure to support the management of students with mTBI. The nature and recovery process of mTBI are briefly described specifically with respect to its effects on school learning and performance. State and local policy considerations are then emphasized to promote implementation of a consistent process. Five key components to building a statewide infrastructure for students with mTBI are described including (1) definition and training of the interdisciplinary school team, (2) professional development of the school and medical communities, (3) identification, assessment, and progress monitoring protocols, (4) a flexible set of intervention strategies to accommodate students' recovery needs, and (5) systematized protocols for active communication among medical, school, and family team members. The need for a research to guide effective program implementation is stressed. Conclusion: This guiding framework strives to assist the development of support structures for recovering students with mTBI to optimize academic outcomes. Until more evidence is available on academic accommodations and other school-based supports, educational systems should follow current best practice guidelines.